The effectiveness of biapenem in the treatment of sepsis - I. V. Shlyk; A. A. Spiridonova; V. A. Panafidina (Вестник анестезиологии и реаниматологии)
The objective was to evaluate the clinical effectiveness and safety of biapenem (Bianem–AF drug) in the treatment of severe forms of infection in ICU patients.Materials and methods. The prospective observational study. At the first stage, microbiological testing of strains (n = 51) isolated from patients in ICU of the Scientific and Clinical Center of Anesthesiology and Intensive Care of the Pavlov University was performed to determine sensitivity to meropenem and biapenem by serial dilution method with the determination of MIC (Minimal Inhibitory Concentration). The genes of serine and metallocarbapenemases were detected by PCR method. At the second stage, patients over 18 years old with the site of infection that required surgical treatment and with clinical and laboratory signs of sepsis were included (n = 19: 11 females, 8 males, mean age 63.4 years). These patients received therapy with biapenem 600 mg every 12 hours as extended infusions over 1 hours (after bolus injection for the first 24 hours). Daily assessment of the severity of the inflammatory reaction and organ dysfunction was conducted to all patients included in the study. Microbiological analysis of biological material obtained from the site of infection has been obtained. Clinical effectiveness was evaluated as recovery/improvement or lack of effect. Adverse effects were recorded.Results. Among 51 isolates of microorganisms: 27 (52.9%) Klebsiella pneumonia, 16 (31%) strains of other representatives of the order Enterobacteriales, 8 (15,6%) non-fermenting gram-negative microorganisms. 48% of Klebsiella pneumoniae isolates were resistant to meropenem and biapenem. All of them had serine (class A and D) and metallo-carbapenemase (class B) genes, as well as their combination. Of the 16 strains of other representatives of the order Enterobacteriales, only 2 (12.5%) were resistant to meropenem and biapenem. Resistance to carbapenems in the non-fermenting gram-negative microorganisms reached 87.5%. The proportion of ESBL producers among carbapenem-sensitive Enterobacteriales reached 93%. The response to biapenem therapy was received in 100% of patients. A day after the start of biapenem administration, a decrease in the level of procalcitonin was noted from 4.65 ng/ml (1.26; 18.8) to 2.2 (1.3; 16.2), after 72 hours – to 1.9 (0.8; 5.0) ng/ ml, by the 7th day – to 0.6 (0.3; 2.5) ng/ml. The median SOFA score decreased from 3.0 (1.5; 4.0) after 24 hours to 2.0 (0,5; 3,5). The average duration of antibacterial therapy was 6 days, the duration of stay in the ICU was two days, and the duration of hospitalization was 9.5 days. There were no adverse effects when using biapenem.Conclusion. Given the high prevalence of ESBL producers and Pseudomonas aeruginosa strains in hospitals, the more favorable safety profile of biapenem compared to other carbapenems, Biapenem appears to be a justified choice for initial empirical therapy MDR sepsis.